The Implementation Model of a Diagnostic Test for English Teachers - ., Sutanti (Indonesian Journal of English Language Studies (IJELS), 2015)
Professionalism in teaching is one of the key factors in the success of an English education program. To keep the teachers‟ professionalism, a refresher program is needed to beconducted to improve teachers‟ competence. To map out the area of teachers‟ competencewhich should be refreshed, a diagnostic test needs designing. After a diagnostic test has beenmade, the implementation should also be well-conducted to get the representative result.Therefore, this study aims to design an alternative implementation model of a diagnostic testfor English teacher. The questionnaire and focus group discussion results show that theproposed model is an appropriate diagnostic test implementation model for teachers. Keywords: implementation model, diagnostic test, refresher program